Cognitive development in children with 22q11.2 deletion syndrome - Sasja N. Duijff; Petra Klaassen; Henriëtte F. N. Swanenburg de Veye; Frits A. Beemer; Gerben Sinnema; Jacob Vorstman (2012)
Background People with 22q11.2 deletion syndrome (velo-cardio-facial syndrome) have a 30-fold risk of developing schizophrenia. In the general population the schizophrenia phenotype includes a cognitive deficit and a decline in academic performance preceding the first episode of psychosis in a subgroup of patients. Findings of cross-sectional studies suggest that cognitive abilities may decline over time in some children with 22q11.2 deletion syndrome. If confirmed longitudinally, this could indicate that one or more genes within 22q11.2 are involved in cognitive decline. Aims To assess longitudinally the change in IQ scores in children with 22q11.2 deletion syndrome. Method Sixty-nine children with the syndrome were cognitively assessed two or three times at set ages 5.5 years, 7.5 years and 9.5 years. Results A mean significant decline of 9.7 Full Scale IQ points was found between ages 5.5 years and 9.5 years. In addition to the overall relative decline that occurred when results were scored according to age-specific IQ norms, in 10 out of a group of 29 children an absolute decrease in cognitive raw scores was found between ages 7.5 years and 9.5 years. The decline was not associated with a change in behavioural measures. Conclusions The finding of cognitive decline can be only partly explained as the result of ‘growing into deficit’; about a third of 29 children showed an absolute loss of cognitive faculties. The results underline the importance of early psychiatric screening in this population and indicate that further study of the genes at the 22q11.2 locus may be relevant to understanding the genetic basis of early cognitive deterioration.